Biological Effects Induced by Non-thermal Ultrasound and Implications for Cancer Therapy: A Review of the Current Literature. (April 2015) - Tang, Justin; Guha, Chandan; Tomé, Wolfgang A.
Recent advancements in imaging and targeting have expanded the utility of ultrasound therapy with increasing attention being paid to the application of ultrasound in cancer therapy. We present in this article a review of the biological effects of non-thermal ultrasound that could find application in cancer treatment in the near and long term. A careful examination of the ultrasound parameters that elicited these observed effects is needed so that one may refine and apply these results for clinical application. Reported biological effects from non-thermal ultrasound have been categorized into mechanical and chemical means of action. Cavitation and acoustic radiation force are the main contributors to sonomechanical effects of ultrasound while reactive oxygen species contribute to its sonochemical effects. These two categories are responsible for observations such as induction of apoptosis in cancer cells, disturbance of the cytoskeleton, enhancement of gene transfection and chemotherapeutic potency, and modulation of cellular proliferation and protein synthesis. In this review we have considered the biological effects of non-thermal ultrasound, the range of parameters at which these biological effects are observed, and the applicability of the observed biological effects to cancer therapy.